Implikasi Dampak Platform (Jalak Loewe) Dalam Penanganan Jalan Rusak Pada Unit Dinas Pekerjaan Umum Bina Marga Provinsi Jawa Timur - Dewi, Deby Cintia; Megawati, Suci (Universitas Negeri Surabaya, 2024)
The Dinas Pekerjaan Umum Bina Marga Province Jawa Timur has created an innovative public service for complaints about damaged roads, namely the Damaged Roads Self Report (Jalak Loewe) application. The positive impact of this application is that handling that was previously manual can be done online so that it can be more effective and efficient. However, the negative impact of the application being implemented is that there are still several problems related to the application, such as the application having errors when logging in, there is no information regarding provincial authority routes and socialization is considered to be lacking. People only need to download this platform on the Google Play Store, then enter their email for registration and add a photo and street address which will be reported, then the complaint will be immediately handled by the department within 1 x 24 hours. According to Indrajit, digitalization of services is defined as a new interaction mechanism (modern era) between the government and the community and other interested groups or stakeholders, namely involving the use of information technology (the internet) with the aim of improving the quality of ongoing services. The research results show that this application has been successful in dealing with damaged roads in the East Java region, although its implementation is still not optimal. This research method uses a qualitative descriptive method. Based on the research results, the suggestions that researchers can give are: 1) It is hoped that they can add information to the provincial authority road menu. 2) It is hoped that they can provide outreach through other social media. 3) It is hoped that they can increase the budget to improve the application system. 4) It is hoped that they can increase employee response.